Product Quality, Price, and Brand Image as Determinants of Purchase Decisions for Wardah Facial Moisturizers - Ni Komang Ayuni Puspita Sari; Satria Bangsawan (International Forum of Researchers and Lecturers, 2025)
This study investigates the impact of product quality, price, and brand image on the purchasing decisions of Wardah facial moisturizer among female students at the Faculty of Economics and Business, University of Lampung. Wardah was selected due to its popularity among young consumers and its reputation as a halal-certified brand offering affordable, high-quality products. Using a quantitative survey method, data were collected from 115 respondents who had purchased the product at least three times. The analysis, conducted through multiple linear regression, reveals that product quality, price, and brand image significantly influence purchase decisions both individually and simultaneously. These results highlight the importance of these factors in consumer decision-making and offer practical insights for cosmetic companies, especially Wardah, in crafting marketing strategies tailored to the preferences of young consumers. Additionally, the findings contribute to the growing body of marketing literature on cosmetic products in the Indonesian context.